Ag-cofe alloy@nc composite CDI material and preparation and application thereof

CN120364808BActive Publication Date: 2026-10-27CENT SOUTH UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510701328.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-28
Publication Date
2026-10-27
Estimated Expiration
2045-05-28

AI Technical Summary

Technical Problem

[0009]针对现有Ag基CDI材料吸附容量不足及循环稳定性差的问题,本发明提供了一种Ag-CoFe合金@NC复合CDI材料,旨在缓冲Ag膨胀,改善CDI电吸附容量、稳定性和选择性

Benefits of technology

[0047]1、本发明提供了一种创新的Ag-CoFe合金@NC复合CDI材料,研究表明,该材料在CDI脱盐过程中展现出显著的Cl-吸附容量提升与结构稳定性优化。所述材料不仅实现了Cl-吸附容量达172.96mg/g(1.6V,1000mg/LNaCl溶液),此外,该电极在50次循环后容量保持率≥90%。相较于传统Ag基材料(循环后容量衰减>15%),其稳定性提升较好,适用于高盐废水与海水淡化场景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120364808B_ABST
    Figure CN120364808B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of electrochemical water treatment, and particularly relates to an Ag-CoFe alloy@NC composite CDI material, a preparation method thereof and application thereof in CDI, wherein the Ag-CoFe alloy@NC composite CDI material comprises a carbon substrate and nanometer active particles dispersedly distributed in the carbon substrate; the carbon substrate is a porous N-doped carbon material; the nanometer active particles comprise nanometer Ag and CoFe alloy, and a heterojunction exists between the Ag and the CoFe alloy; the nanometer active particles and the carbon substrate are coupled through C-N-M chemical bonds, wherein M is at least one of Ag, Co and Fe. Furthermore, the application also provides the preparation and application of the material. The material has excellent electric adsorption capacity and selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of water treatment, specifically relating to CDI treatment materials. Background Technology

[0002] Desalination of seawater and high-salinity brackish water is considered an important way to obtain usable freshwater. Among various desalination technologies, capacitive deionization (CDI) technology has gradually become a research hotspot due to its unique energy recovery potential, low operating cost, ease of operation, and regenerable electrode materials. This technology drives ions in the water to migrate to the electrode surface and achieve adsorption and storage by applying an external electric field. It can partially recover electrical energy while completing desalination, demonstrating significant sustainable development characteristics.

[0003] The core breakthrough in CDI technology relies on the development of high-performance electrode materials. While widely used porous carbon-based electrode materials (such as activated carbon and carbon nanotubes) possess excellent conductivity and pore structure, their ion adsorption capacity is generally below 30 mg / g. Furthermore, carbon electrodes are prone to side reactions during electrochemical processes (such as co-ion repulsion and hydrogen / oxygen evolution reactions), leading to a significant reduction in charge efficiency (typically <80%) and desalination selectivity. To overcome this bottleneck, silver (Ag)-based electrode materials based on the Faraday redox reaction are considered ideal candidates for next-generation CDI devices due to their high theoretical desalination capacity (248 mAh / g) and high charge utilization efficiency.

[0004] The desalination mechanism of silver-based electrodes originates from their specific electrochemical conversion reaction. The redox potential is +0.22V (vs. RHE). Under an electric field, Ag and Cl- react reversibly to form insoluble AgCl, thus achieving selective capture and release of chloride ions. Compared to traditional carbon electrodes, silver-based materials not only have lower reaction overpotentials and higher specific capacitances, but the high reversibility of their redox process also significantly improves cycle stability. Further research shows that the phase transition kinetics of AgCl / Ag can be optimized through nanostructure control, such as reducing the silver particle size (<10nm) to shorten the ion diffusion path, or constructing a carbon-silver composite interface to mitigate the volume expansion effect (AgCl has a volume expansion rate of approximately 225%), thereby suppressing electrode pulverization and extending service life.

[0005] Existing technologies also report some applications of CDI technology using silver-carbon composite materials. For example, Chinese patent document CN115463625A discloses a nanowire-lignin-derived carbon composite aerogel, its preparation method, and its application. Chinese patent document CN113257586A discloses a method for preparing and applying a silver-carbon composite electrode material. Chinese patent document CN111777068A discloses a novel chloride ion removal material Ti3C2T. x Preparation methods and applications of / Ag.

[0006] Although silver (Ag)-based electrodes have demonstrated superior dechlorination performance in capacitive deionization (CDI) technology and have become a research focus in both academia and industry, their practical application is still limited by the structural instability of the electrode material during cycling. Under the influence of an electrochemical field, Ag and Cl- react reversibly to form AgCl, due to the difference in their molar volumes (AgCl: 25.7 cm⁻¹). 3 / mol vs. Ag: 10.3cm 3 The expansion stress ( / mol) causes a volume expansion of up to 225%. This expansion stress induces the initiation and propagation of grain boundary cracks within the Ag / C composite material, leading to the stripping and pulverization of active material from the carbon matrix, ultimately resulting in a significant deterioration of the electrode's cycle life (capacity retention <85% after 50 cycles) and mechanical integrity (Adv. Mater. 2022, 34, 2107284).

[0007] To overcome the aforementioned bottlenecks, nanostructuring strategies have been widely adopted to improve the stability of Ag-based electrodes: strain modulation effect: the absolute volume change of nanoparticles and their cubic particle size (d 3 The effect is inversely proportional; when the Ag particle size decreases from the micrometer level (>1 μm) to 10 nm, the volumetric strain of a single particle decreases to the order of one-thousandth, thereby significantly suppressing the structural distortion of the macroscopic electrode (NanoLett. 2023, 23, 5678); enhanced kinetics: nano-sizing can shorten the ion diffusion path (diffusion time τ∝d). 2 / D), and exposes high-density surface active sites (specific surface area SSA∝6 / (ρd)), significantly improving reaction kinetics and charge storage efficiency (ACS Energy Lett. 2021, 6, 2345).

[0008] However, the synthesis of traditional Ag nanoparticles relies on high-temperature thermal reduction (>600℃), which leads to the following problems: sintering and coarsening: at high temperatures, the Ostwald ripening effect drives particle migration and interface fusion, increasing the average particle size from 10nm to 80nm, and resulting in a loss of more than 70% of the active specific surface area (Chem. Eng. J. 2023, 451, 138912); poor dispersion uniformity: due to their high surface energy, nanoparticles are prone to van der Waals force-driven self-aggregation, requiring complex surface modification (such as thiol molecules) or external field-assisted dispersion (such as ultrasound), increasing the process cost (J. Mater. Chem. A 2022, 10, 12345). Summary of the Invention

[0009] To address the issues of insufficient adsorption capacity and poor cycling stability of existing Ag-based CDI materials, this invention provides an Ag-CoFe alloy@NC composite CDI material, which aims to buffer Ag expansion and improve the electroadsorption capacity, stability, and selectivity of CDI.

[0010] The second objective of this invention is to provide a method for preparing the Ag-CoFe alloy@NC composite CDI material and its application as a CDI catalytic active material.

[0011] The third objective of this invention is to provide a CDI electrode and device containing the Ag-CoFe alloy@NC composite CDI material.

[0012] To address the problems of unsatisfactory adsorption capacity, significant volume expansion, and unsatisfactory adsorption stability in Ag / C composite CDI materials, this invention provides the following improvement solutions:

[0013] Ag-CoFe alloy@NC composite CDI material, comprising a carbon substrate and nano-active particles dispersed therein; wherein the carbon substrate is a porous N-doped carbon material (also known as NC); the nano-active particles comprise nano-sized Ag and CoFe alloys, wherein a heterogeneous interface exists between the Ag and CoFe alloys.

[0014] The nano-active particles and the carbon substrate are coupled through CNM chemical bonds, where M = at least one of Ag, Co, and Fe.

[0015] This invention provides a novel Ag-CoFe alloy@NC composite material, which uses NC carbon as a substrate and disperses Ag-CoFe composite particles therein. A heterogeneous interface exists between Ag and CoFe alloy, and a chemical chelation effect exists between the carbon substrate and the active particles. Studies have shown that the combination of the carbon substrate and the special nano-active particles achieves synergy, enabling a micro-electric field between the active particles. This improves the electroadsorption effect of CDI, for example, by improving the electroadsorption capacity and selectivity. Furthermore, it buffers Ag expansion and improves electroadsorption stability.

[0016] In this invention, the phase of the CoFe alloy is at least one of Co7Fe3 and Co3Fe7; preferably Co7Fe3. Research in this invention shows that the preferred Co7Fe3 phase further facilitates the bonding of Ag heterojunction surfaces, and further enhances the CDI activity and stability of the material.

[0017] Preferably, the molar ratio of Ag:Co:Fe in the Ag and CoFe alloy is 1:(0.5~2):(0.5~2); more preferably 1:1:0.5~2; and most preferably 1:1:0.5.

[0018] Preferably, the particle size of the nano-active particles is 5–15 nm, and D90 ≤ 12 nm.

[0019] Preferably, the Ag-CoFe alloy@NC composite CDI material has a hierarchical porous structure and a specific surface area ≥1200 m². 2 / g, porosity ≥80%.

[0020] Preferably, the content of nano-active particles in the Ag-CoFe alloy@NC composite CDI material is 10 wt.% to 30 wt.%.

[0021] Preferably, in the carbon substrate, the proportion of nitrogen-containing functional groups is ≥5 wt.%, wherein the nitrogen-containing functional groups include pyridine nitrogen and pyrrole nitrogen; the degree of graphitization ID / IG value is ≤0.8, and the electrical conductivity is ≥50 S / cm.

[0022] The present invention also provides a method for preparing the Ag-CoFe alloy@NC composite CDI material, wherein a mixed raw material containing Ag source, Fe source, Co source and nitrogen-containing carbon source is calcined at a temperature of 400-600°C to obtain the Ag-CoFe alloy@NC composite CDI material; wherein the molar ratio of Ag:Co:Fe in Ag source, Fe source and Co source is 1:(0.5-2):(0.5-2).

[0023] This invention innovatively calcines a mixture of Ag, Fe, Co, and nitrogen-containing carbon sources in the specified proportions at the specified temperature. This promotes Fe-Co alloying and induces a dominant alloying phase. Furthermore, it facilitates Ag nucleation on the Fe-Co alloy and promotes the formation of a bonding interface. In addition, the preparation method promotes chemical chelation between the active particles and the carbon substrate, thus achieving a confined nucleation effect on the active particles and improving their mechanical strength and expansion resistance. Studies have shown that the material prepared by the method of this invention can effectively improve the electroadsorption capacity, stability, and selectivity of Ag-based CDI materials.

[0024] In this invention, the combination of Ag, Fe, Co, and N-containing carbon sources, their proportions, and the calcination temperature are key to achieving Fe-Co alloying, controlling the alloyed metal phase, facilitating interfacial bonding with Ag, confining active particles, and improving CDI activity and stability. The study also found that optimizing the N-containing carbon source, its proportions, and the calcination temperature helps to further improve the physicochemical properties and stability of the prepared material.

[0025] In this invention, the Ag source, Fe source, and Co source are water-soluble salts of their respective metals.

[0026] Preferably, the Ag source is silver nitrate; the Fe source is ferric nitrate; and the Co source is cobalt nitrate.

[0027] Preferably, the molar ratio of Ag:Co:Fe in the Ag source, Fe source, and Co source is 1:1:0.5 to 2; most preferably, it is 1:1:0.5. This invention demonstrates that the innovative use of a combination of Ag, Fe, and Co sources in the aforementioned process facilitates the confined formation of the alloy and promotes chemical interfacial interaction between the Ag-alloy and the carbon substrate. Furthermore, the study shows that controlling the Ag:Co:Fe molar ratio within the preferred range, combined with the overall process such as the nitrogen-containing carbon source and calcination temperature, helps to further form the Co7Fe3 phase, improving its phase content and stability, and further enhancing its CDI activity and stability.

[0028] In this invention, the nitrogen-containing carbon source is at least one of PVP and PAN; preferably PVP. Research in this invention shows that the preferred PVP further facilitates the confined growth of the active particles' phase and interface, and also facilitates the chelation and anchoring of the active particles, thus helping to further enhance the CDI activity and stability of the prepared material.

[0029] Preferably, the weight ratio of total metal elements in the Ag, Fe, and Co sources to the nitrogen-containing carbon source is 0.1–0.5:1, and more preferably 0.15–0.25:1. Preferably, 1–5 mmol of total metals is added per gram of nitrogen-containing carbon source, more preferably 2–3 mmol.

[0030] In this invention, the mixed raw materials are obtained by solid-phase mixing of the raw materials or by liquid-phase mixing followed by solvent removal. Preferably, the raw materials can be dissolved in water and then mixed, and the pH of the system can be controlled to be acidic, for example, 4 to 6, followed by solvent removal to obtain the mixed raw materials.

[0031] The atmosphere during the roasting process is a protective atmosphere, or a protective atmosphere-hydrogen mixture, wherein the protective atmosphere includes at least one of nitrogen and an inert gas.

[0032] This invention demonstrates that the combined calcination of the required Ag:Co:Fe ratio and N-containing carbon precursor, along with precise temperature control, facilitates the regulation of the Fe-Co alloy metallic phase. For example, it is expected to induce a Co7Fe3 dominant phase, which promotes Ag-induced growth and the formation of highly active and stable heterojunctions. This, in turn, is expected to generate micropotentials during CDI, enhancing the CDI effect and stability. The study also shows that the described preparation process can achieve good alloy phase preparation at relatively low calcination temperatures, resulting in superior CDI electroadsorption activity and stability.

[0033] In this invention, the calcination temperature is 450–550°C; more preferably 480–520°C.

[0034] Preferably, the roasting time is 2 to 4 hours.

[0035] The present invention also provides Ag-CoFe alloy@NC composite CDI material prepared by the above preparation method.

[0036] The present invention also provides an application of the Ag-CoFe alloy@NC composite CDI material, using it as a CDI active material.

[0037] In this invention, the Ag-CoFe alloy@NC composite CDI material described herein can be used as a CDI active material for CDI treatment based on known methods.

[0038] For example, as an alternative, it can be used as a CDI active material for the electroadsorption of halide anions, including chloride ions.

[0039] The present invention also provides a CDI electrode material, comprising an active material, wherein the active material comprises the Ag-CoFe alloy@NC composite CDI material of the present invention.

[0040] The CDI electrode material described in this invention, apart from the CDI active material described in this invention, may contain other known components and parts, or may be reasonably adjusted based on known methods.

[0041] For example, in the active material, the content of the Ag-CoFe alloy@NC composite CDI material is above 70 wt.%;

[0042] Preferably, the CDI electrode material may also contain a binder and a conductive agent.

[0043] The present invention also provides a CDI electrode, comprising a current collector and a CDI electrode material composite thereon, wherein the CDI electrode material is the CDI electrode material described in the present invention.

[0044] The present invention also provides a CDI device comprising a CDI electrode containing the Ag-CoFe alloy@NC composite CDI material described in the present invention.

[0045] In this invention, the CDI process can be carried out based on known methods. In addition, the conditions of the CDI process can be adjusted based on known raw materials. For example, the voltage in the CDI process can be above 1V, for example, it can be 1 to 1.6V; further, it can be 1.2 to 1.6V.

[0046] Beneficial effects

[0047] 1. This invention provides an innovative Ag-CoFe alloy@NC composite CDI material. Studies have shown that this material exhibits a significant improvement in Cl- adsorption capacity and optimized structural stability during CDI desalination. The material not only achieves a Cl- adsorption capacity of 172.96 mg / g (1.6V, 1000 mg / L NaCl solution), but also maintains a capacity retention rate of ≥90% after 50 cycles. Compared to traditional Ag-based materials (capacity decay >15% after cycling), it demonstrates better stability and is suitable for high-salinity wastewater and seawater desalination applications.

[0048] 2. The present invention, through the preparation method described above, based on the combination of components, proportions, and temperature, can construct materials with special physicochemical properties. Moreover, the materials with special physicochemical properties prepared by the method can be adapted to the requirements of CDI applications and can obtain excellent electro-adsorption activity and stability. In addition, the materials described in the present invention can obtain good CDI adsorption effects under a wide voltage system.

[0049] 3. The Ag-CoFe alloy@NC composite CDI material provided by this invention breaks through the contradiction of "capacity-stability-kinetics" of traditional CDI electrodes through multi-metal synergy and chemical confinement design, and its effect directly addresses the needs of industrial-grade high-salt wastewater treatment and extreme environment applications. Attached Figure Description

[0050] Figure 1 The images show the XRD patterns of the electrode materials Ag@NC, CoFe@NC, and Ag-CoFe alloy@NC prepared in Examples 1 and Comparative Examples 1-2.

[0051] Figure 2 The images show TEM images and size distribution histograms of the Ag-CoFe alloy@NC prepared in Example 1, where a is the TEM image and b is the size distribution histogram of Ag particles in the Ag-CoFe alloy@NC.

[0052] Figure 3 The image shows the TEM-EDS diagram of the Ag-CoFe alloy@NC material prepared in Example 1, where a is the TEM image and b to g are the elemental distribution diagrams.

[0053] Figure 4 The images shown are SEM-EDS images of the Ag-CoFe alloy@NC material prepared in Example 1, where a to d are SEM images under different viewing windows, and e to j are element distribution maps.

[0054] Figure 5 Thermogravimetric curves of the materials prepared in Examples 1-2 and Comparative Examples 1-2 in air atmosphere.

[0055] Figure 6 The figures show the electrochemical performance test results of the materials prepared in Examples 1-2 and Comparative Examples 1-2. In the figures, a is the cyclic voltammetry curve of Ag-CoFe alloy@NC at a scan rate of 0.5-5 mV / s; b is the galvanostatic charge-discharge curve of Ag@NC, CoFe@NC and Ag-CoFe alloy@NC at 0.1 A / g; c is the electrochemical impedance spectroscopy of Ag@NC, CoFe@NC and Ag-CoFe alloy@NC; and d is the test of Ag-CoFe alloy@NC after 100 cycles at a current density of 1 A / g.

[0056] Figure 7 The graph shows the dechlorination performance of the materials in Example 1 and Comparative Examples 1-3 in a 1000 mg / L NaCl solution under constant voltage of 1.4 V.

[0057] Figure 8 The dechlorination performance of the Ag-CoFe alloy@NC prepared in Example 1 in a 1000 mg / L NaCl solution at a voltage of 1.0-1.6 V. Detailed Implementation

[0058] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0059] The technical solutions of the various embodiments of the present invention can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such combination of technical solutions does not exist and is not within the scope of protection claimed by the present invention.

[0060] Those skilled in the art should understand that, as an explanation of the accompanying drawings of this invention, without affecting the understanding of this invention, "intensity" in the drawings can be understood as intensity, and "cycle number" can be understood as the number of cycles.

[0061] To address the issue of volume expansion in existing Ag electrodes during electrochemical dechlorination, this invention provides a method for preparing carbon-supported nanoalloy material Ag-CoFe alloy@NC, comprising the following steps:

[0062] S1, add silver nitrate (AgNO3), cobalt nitrate (Co(NO3)2·6H2O), and ferric nitrate (Fe(NO3)3·9H2O) in a molar ratio of 1:(0.5~2):(0.5~2) to deionized water and stir until completely dissolved to form solution one;

[0063] S2, dissolve polyvinylpyrrolidone (PVP, K30) in deionized water to prepare a solution with a concentration of 10±5wt%;

[0064] S3, add solution one dropwise to solution two, and sonicate at a power of 300±100W for 30±10min to form a homogeneous mixed solution three;

[0065] S4. Stir the mixed solution for 1-5 hours to complete the in-situ anchoring of the metal-PVP complex on the carbon matrix.

[0066] S5. After the reaction is complete, the solution is dried under vacuum to obtain Ag-Co-Fe-PVP / carbon precursor.

[0067] S6. The precursor is placed in a tube furnace and calcined in an Ar atmosphere for 2-4 hours. After natural cooling, the composite material is obtained.

[0068] In order to achieve efficient adsorption of chloride ions, the present invention also provides a method for electro-adsorption of chloride ions, wherein the Ag-CoFe alloy@NC material as described in any of the above embodiments is used on the electrode of a capacitive deionization device, and the chloride ions in the chloride ion solution are adsorbed by the capacitive deionization device.

[0069] Specifically, the process of using the Ag-CoFe alloy@NC material on the electrode of a capacitive deionization device may include: mixing the Ag-CoFe alloy@NC material, polyvinylidene fluoride and carbon black in a mass ratio of 80wt%:10wt%:10wt%, adding N-methylpyrrolidone, grinding into a slurry and then coating it onto a conductive current collector.

[0070] Furthermore, during the adsorption of chloride ions in the chloride ion solution by the aforementioned capacitor deionization device, the Cl in the chloride ion solution... - The initial concentration can be 500-3000 mg / L, and the applied voltage of the capacitor deionization device can be 1.0-1.6V.

[0071] AC refers to commercially purchased activated carbon (Jiangsu Xianfeng Nanomaterials Technology Co., Ltd., with a specific surface area of ​​1800 m²). 2 / g).

[0072] To further illustrate the present invention, examples are given below:

[0073] Example 1

[0074] This embodiment describes a method for preparing a carbon-supported nanoalloy material, Ag-CoFe alloy@NC, comprising the following steps:

[0075] (1) Under stirring conditions, 1 mmol silver nitrate (AgNO3), 1 mmol cobalt nitrate (Co(NO3)2·6H2O) and 0.5 mmol ferric nitrate (Fe(NO3)3·9H2O) were dissolved in 50 mL of deionized water to form a homogeneous solution.

[0076] (2) Dissolve 1g of nitrogen-containing carbon source (polyvinylpyrrolidone, PVP, K30) in 10mL of deionized water to obtain a homogeneous solution II;

[0077] (3) Add solution one dropwise to solution two (the total weight of metal elements in solution one is 0.2:1, that is, 2.5 mmol of metal is used per gram of PVP), and then sonicate at 300W for 30 min to obtain a uniform metal-PVP complex mixed solution three.

[0078] (4) Transfer the mixed solution into a glass container (30% filling rate) and react at 30°C for 2 hours to complete the chemical coordination anchoring of the metal source and the carbon source;

[0079] (5) After the mixed coordination reaction was completed, the mixture was dried under vacuum at 100℃ for 24 h to obtain Ag-Co-Fe-PVP / carbon precursor;

[0080] (6) The precursor was placed in a tube furnace and heated to 500°C at 5°C / min under an Ar atmosphere. The temperature was held for 3 hours and then naturally cooled to obtain Ag-CoFe alloy@NC (specifically Ag-Co7Fe3@NC) composite material.

[0081] Comparative Example 1

[0082] Compared with Example 1, the only difference is that silver nitrate is omitted in step 1, the proportions of other metals and the proportions of total metal and PVP in step 3 are the same as in Example 1, and the final material is labeled as CoFe alloy@NC material (also labeled as Co7Fe3@NC).

[0083] Comparative Example 2

[0084] Compared with Example 1, the only difference is that in step 1, cobalt nitrate and iron nitrate were not added, and the ratio of total metal and PVP in step 3, as well as other operations and parameters, are the same as in Example 1. The final material is labeled as Ag@NC material.

[0085] Comparative Example 3

[0086] Compared to Example 1, commercial AC was used as the CDI active material.

[0087] AC refers to commercially purchased activated carbon (Jiangsu Xianfeng Nanomaterials Technology Co., Ltd., with a specific surface area of ​​1800 m²). 2 / g).

[0088] See XRD diagram Figure 1 The peak shape of the Ag-CoFe alloy@NC is completely consistent with the standard peaks in Ag standard card PDF#04-004-0783 and Co7Fe3 standard card PDF#00-050-0795, indicating the successful preparation of the Ag-CoFe alloy@NC material. See the TEM-EDS analysis diagram below. Figure 2 , Figure 3 This provides a clear and intuitive understanding of the structure, Ag size, and distribution of the Ag-CoFe alloy@NC. The Ag particles have a diameter of 2.4-3.6 nm and a D50 of approximately 2.89 nm. (EDS energy dispersive spectroscopy image) Figure 3The ag) shows a uniformly dispersed overall elemental mapping of silver, cobalt, and iron, indicating the successful preparation of Ag-CoFe alloy@NC material.

[0089] From SEM-EDS ( Figure 4 The analysis revealed that the Ag-CoFe alloy@NC material has a honeycomb porous structure on its surface, which provides a structural channel for ions in the solution to enter the material during the desalination process. The EDS elemental mapping of the surface pore structure showed that silver, cobalt and iron elements were uniformly dispersed on the material surface, indicating that the material has good elemental dispersion and uniformity. The diffuse distribution of silver prevents a large number of active adsorption sites from overlapping and reduces agglomeration, resulting in a higher adsorption capacity than comparative examples 1-3.

[0090] In addition, thermogravimetric analysis (TGA) was used to evaluate the component content of the Ag-CoFe alloy@NC materials prepared in Example 1, Comparative Example 1, and Comparative Example 2, as well as the component content of the CoFe alloy@NC materials and Ag@NC materials. Figure 5 The slight mass loss from room temperature to 260°C can be attributed to the evaporation of absorbed water, while the subsequent weight increase and loss originate from the oxidation reactions of the CoFe alloy and carbon, respectively. The calculated carbon contents in the Ag-CoFe alloy@NC material, CoFe alloy@NC material, and Ag@NC material are 51.51%, 37.98%, and 16.12%, respectively. Higher carbon content indicates a tighter bond between PVP and the metal source during carbonization, and better coating of the metal source, which is beneficial to improving material stability.

[0091] Application Test 1: Electrochemical Performance Test

[0092] This experiment aims to investigate the effects of different scan rates (0.5-30 mV / s). -1 The electrochemical performance of Ag-CoFe alloy@NC composite electrode material prepared under ) was investigated, revealing the influence mechanism of trimetallic synergistic effect on dechlorination performance.

[0093] The specific operation process is as follows: Mix 8 mg of active material (the material ultimately prepared in each case), 1 mg of conductive carbon black (Super P), and 1 mg of polyvinylidene fluoride (PVDF) binder, add 0.6 mL of N-methylpyrrolidone (NMP), ultrasonically disperse for 30 min, and stir to form a homogeneous slurry; then take 50 μL of the slurry and evenly coat it on a 1×1 cm... 2 The working electrode was prepared by vacuum drying the carbon paper surface at 120℃ for 12 hours. Electrochemical testing employed a three-electrode system, using a platinum sheet as the counter electrode, Ag / AgCl (3M KCl) as the reference electrode, and 1M NaCl solution as the electrolyte. The following tests were performed using an electrochemical workstation:

[0094] (1) Cyclic voltammetry (CV): scan rate 1 mV / s, potential range -0.2 to 1.0 V (vs. Ag / AgCl);

[0095] (2) Constant current charge-discharge (GCD): current density 0.1 A / g;

[0096] (3) Electrochemical impedance (EIS): Frequency range 100kHz~0.01Hz, amplitude 5mV;

[0097] (4) Long cycle test: current density 1A / g, 1000 cycles.

[0098] The cyclic voltammetry curve of the Ag-CoFe alloy@NC material obtained in Example 1 was measured at a scan rate of 1 mV / s. Figure 6 a) All electrodes exhibited symmetrical redox peaks. The CV curves of each electrode showed a distinct oxidation peak at 0.12 V and a distinct reduction peak at -0.05 V (relative to Ag / AgCl), which is related to the reversible electrochemical conversion between Ag and AgCl.

[0099] The charge-discharge curves of the Ag-CoFe alloy@NC material obtained in Example 1 at a current density of 0.1 A / g were measured. Figure 6 b) Ag-CoFe alloy@NC showed the longest discharge time. Figure 6 c represents the electrochemical impedance spectroscopy, where the Ag-CoFe alloy@NC shows a minimum charge transfer resistance of 2.14 Ω. Figure 6 d represents the Ag-CoFe alloy@NC material after 100 charge-discharge cycles at a current density of 1 A / g, with a capacity retention of >80% after 100 cycles.

[0100] Application Test 2: Constant Voltage CDI Test

[0101] CDI tests were performed on the materials finally prepared in each case. The CDI electrode was prepared as follows: 80 wt% of the active material (prepared in each case), 10 wt% of acetylene black, and 10 wt% of PVDF were dissolved in 1 mL of NMP, then sonicated and stirred for 30 minutes to form a homogeneous slurry. 1 mL of the mixed slurry was coated onto a titanium plate (effective area 5 × 5 cm). 2 The CDI electrode was dried overnight at 120°C. The resulting CDI electrode was assembled into a CDI unit, a voltage was applied between the positive and negative electrodes, and the salt solution to be treated was delivered to the CDI unit by a peristaltic pump to test the electrochemical performance of the CDI device.

[0102] The applied voltage of the above-mentioned capacitor deionization device was set to 1.4V, the adsorption time to 40min, and the concentration of the NaCl solution to 1000mg / L. For example... Figure 7As shown, the dechlorination capacity of the Ag-CoFe alloy@NC prepared in Example 1 of this invention can reach 139.96 mg / g.

[0103] Application Test 3: CDI Test at Different Voltages: CDI Electrode Preparation: 80 wt% of the active material (materials prepared in each case), 10 wt% of acetylene black, and 10 wt% of PVDF were dissolved in 1 mL of NMP, then sonicated and stirred for 30 minutes to form a homogeneous slurry. 1 mL of the mixed slurry was coated onto a titanium plate (effective area 5 × 5 cm). 2 The NaCl solution was dried overnight at 120°C. The resulting CDI electrodes were assembled into a CDI unit. Different voltages were applied between the positive and negative electrodes, and the salt solution to be treated was delivered to the CDI unit via a peristaltic pump. The electrochemical performance of the CDI device was then tested. The applied voltage of the above-mentioned capacitive deionization device was set to 1.0-1.6V, the adsorption time to 40min, and the concentration of the NaCl solution to 1000mg / L.

[0104] like Figure 8 As shown, the dechlorination capacities of Ag-CoFe alloy@NC at voltages of 1.0V, 1.2V, 1.4V, and 1.6V are 82.55mg / g, 96.26mg / g, 139.96mg / g, and 172.96mg / g, respectively.

[0105] Application Test 4: CDI Cycle Test

[0106] CDI electrode preparation: 80 wt% of the active material (material prepared in each case), 10 wt% of acetylene black, and 10 wt% of PVDF were dissolved in 1 mL of NMP, then sonicated and stirred for 30 minutes to form a homogeneous slurry. 1 mL of the mixed slurry was coated onto a titanium plate (effective area 5 × 5 cm). 2 The CDI electrodes were then dried overnight at 120°C. The resulting CDI electrodes were assembled into a CDI unit, and different voltages were applied between the positive and negative electrodes. The salt solution to be treated was delivered to the CDI unit by a peristaltic pump, and the electrochemical performance of the CDI device was tested.

[0107] The applied voltage of the above-mentioned capacitive deionization device was set to 1.2V, with each cycle consisting of 40 min of adsorption and 40 min of desorption. The concentration of the NaCl solution was 1000 mg / L. The Ag-CoFe alloy@NC maintained 95% of its dechlorination capacity after 50 cycles at 1.2V.

[0108] Table 1 shows the CDI capacity on the first lap and the capacity retention rate after 50 laps for each case:

[0109] Table 1

[0110] Example 1 95% Comparative Example 1 83.56% Comparative Example 2 63.32% Comparative Example 3 59.35%

[0111] Example 2

[0112] Compared to Example 1, the only difference is that the molar ratio of Ag, Co, and Fe in step 1 is changed. All experimental groups are as follows:

[0113] Group A: The molar ratio of Ag, Co, and Fe is 1:1:1;

[0114] Group B: The molar ratio of Ag, Co, and Fe is 1:1:2;

[0115] Compared to Group A: the molar ratio of Ag, Co, and Fe is 1:1:0;

[0116] Compared to Group B, the molar ratio of Ag, Co, and Fe is 1:0:0.5;

[0117] Compared to group C: the molar ratio of Ag, Co, and Fe is 0:1:0;

[0118] The total amount of metal source used in step 3, as well as other operations and tests, are the same as in Example 1.

[0119] The adsorption capacities of different experimental groups are shown in Table 2;

[0120] Table 2

[0121]

[0122] In Examples 2A and 2B, the calcined products contained a composite phase of Co7Fe3 and Co3Fe7. Compared to the pure Co7Fe3 phase in Example 1, the effect was somewhat reduced.

[0123] Furthermore, as can be seen from the comparison groups A to C in Examples 1, Comparative Examples 1-2, and Examples 2, the use of the ternary metals described in this invention and the control of the proportions can achieve synergy, which is beneficial for alloy formation and optimization of alloy phases, thereby obtaining excellent CDI activity.

[0124] Example 3

[0125] Compared with Example 1, the only difference is that the type of N-containing carbon source in step 2 is changed; all other operations and parameters are the same as in Example 1. All experimental groups are as follows:

[0126] Group A: The carbon source containing nitrogen is PVP, and in step 3, the weight ratio of total metal to PVP is 1.5:1;

[0127] Group B: The nitrogen-containing carbon source is replaced with an equal amount of PAN;

[0128] Compared to Group A: the nitrogen-containing carbon source was replaced with an equal amount of PEG;

[0129] The adsorption capacity of materials prepared based on different nitrogen-containing carbon sources for chlorine is shown in Table 3.

[0130] Table 3

[0131]

[0132] The results in Table 3 show that the use of N-containing carbon sources, especially PVP, can unexpectedly synergize with the process, which helps to further construct the Co7Fe3 active phase, facilitates its chemical confinement and stable interfacial bonding, and is more conducive to the CDI performance of the material.

[0133] Example 4

[0134] Compared with Example 1, the only difference is that the temperature in step 6 is changed; all other operations and parameters are the same as in Example 1. The experimental groups are as follows:

[0135] Group A: Temperature 400℃;

[0136] Group B: Temperature 550℃, calcination time 2.5h;

[0137] Group C: Temperature is 600℃;

[0138] Compared to Group A: the temperature was 300℃;

[0139] Compared to Group B: the temperature was 700℃;

[0140] Compared to Group C: the temperature was 800℃;

[0141] All other operations, parameters, and tests are the same as in Example 1;

[0142] Results Table 4

[0143] Table 4

[0144]

[0145] Studies have shown that using temperatures between 400 and 600°C, especially between 450 and 550°C, is beneficial for synergistic process integration to form the special phase. In particular, at the preferred temperatures, it is beneficial for the synergistic formation of the Co7Fe3 active phase, which is conducive to obtaining better CDI activity.

[0146] The above technical solutions of the present invention are merely preferred embodiments of the present invention and do not limit the patent scope of the present invention. All equivalent structural transformations made under the technical concept of the present invention using the contents of the present invention specification and drawings, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.

Claims

1. An Ag-CoFe alloy@NC composite CDI material, characterized in that, It includes a carbon substrate and nano-active particles dispersed therein; wherein the carbon substrate is a porous N-doped carbon material; the nano-active particles include nano-sized Ag and CoFe alloys, wherein there is a heterogeneous interface between the Ag and CoFe alloys. The nano-active particles and the carbon substrate are coupled via CNM chemical bonds, where M is at least one of Ag, Co, and Fe. The phase of the CoFe alloy is at least one of Co7Fe3 and Co3Fe7; The molar ratio of Ag:Co:Fe in the Ag and CoFe alloy is 1:(0.5~2):(0.5~2); In the carbon substrate, the proportion of nitrogen-containing functional groups is ≥5 wt.%, wherein the nitrogen-containing functional groups include pyridine nitrogen and pyrrole nitrogen; the degree of graphitization ID / IG value is ≤0.8, and the electrical conductivity is ≥50 S / cm; The preparation method of the Ag-CoFe alloy@NC composite CDI material is as follows: a mixed raw material containing Ag source, Fe source, Co source and nitrogen-containing carbon source is calcined at a temperature of 400~600℃ to obtain the Ag-CoFe alloy@NC composite CDI material. The molar ratio of Ag:Co:Fe in Ag source, Fe source, and Co source is 1:(0.5~2):(0.5~2).

2. The Ag-CoFe alloy@NC composite CDI material as described in claim 1, characterized in that, The molar ratio of Ag:Co:Fe in Ag and CoFe alloys is 1:1:0.5~2.

3. The Ag-CoFe alloy@NC composite CDI material as described in claim 2, characterized in that, The molar ratio of Ag:Co:Fe in the Ag and CoFe alloy is 1:1:0.

5.

4. The Ag-CoFe alloy@NC composite CDI material as described in claim 1, characterized in that, The particle size of the nano-active particles is 5~15 nm, and D90≤12 nm.

5. The Ag-CoFe alloy@NC composite CDI material as described in claim 1, characterized in that, Ag-CoFe alloy@NC composite CDI material has a hierarchical porous structure and a specific surface area ≥1200 m². 2 / g, porosity ≥80%.

6. The Ag-CoFe alloy@NC composite CDI material as described in claim 1, characterized in that, The content of nano-active particles in Ag-CoFe alloy@NC composite CDI material is 10wt.%~30wt.%.

7. A method for preparing the Ag-CoFe alloy@NC composite CDI material according to any one of claims 1 to 6, characterized in that, The Ag-CoFe alloy@NC composite CDI material is prepared by calcining a mixture of Ag source, Fe source, Co source and nitrogen-containing carbon source at a temperature of 400~600℃. The molar ratio of Ag:Co:Fe in Ag source, Fe source, and Co source is 1:(0.5~2):(0.5~2).

8. The preparation method of the Ag-CoFe alloy@NC composite CDI material as described in claim 7, characterized in that, Ag source, Fe source, and Co source are water-soluble salts of their respective metals.

9. The preparation method of the Ag-CoFe alloy@NC composite CDI material as described in claim 8, characterized in that, The Ag source is silver nitrate; the Fe source is iron nitrate; and the Co source is cobalt nitrate.

10. The preparation method of the Ag-CoFe alloy@NC composite CDI material as described in claim 8, characterized in that, The molar ratio of Ag:Co:Fe in Ag source, Fe source, and Co source is 1:1:0.5~2.

11. The preparation method of the Ag-CoFe alloy@NC composite CDI material as described in claim 10, characterized in that, The molar ratio of Ag:Co:Fe in the Ag source, Fe source, and Co source is 1:1:0.

5.

12. The preparation method of the Ag-CoFe alloy@NC composite CDI material as described in claim 7, characterized in that, The nitrogen-containing carbon source is at least one of PVP and PAN.

13. The preparation method of the Ag-CoFe alloy@NC composite CDI material as described in claim 7, characterized in that, The weight ratio of total metal elements to nitrogen-containing carbon sources in Ag, Fe, and Co sources is 0.1 to 0.5:

1.

14. The preparation method of the Ag-CoFe alloy@NC composite CDI material as described in claim 13, characterized in that, The weight ratio of total metal elements to nitrogen-containing carbon sources in Ag, Fe, and Co sources is 0.15~0.25:

1.

15. The preparation method of the Ag-CoFe alloy@NC composite CDI material as described in claim 7, characterized in that, Mixed raw materials are obtained by solid-phase mixing of the raw materials, or by liquid-phase mixing followed by solvent removal.

16. The preparation method of the Ag-CoFe alloy@NC composite CDI material as described in claim 7, characterized in that, The atmosphere during the roasting process is a protective atmosphere, or a protective atmosphere-hydrogen mixture, wherein the protective atmosphere includes at least one of nitrogen and an inert gas.

17. The preparation method of the Ag-CoFe alloy@NC composite CDI material as described in claim 7, characterized in that, The roasting temperature is 450~550℃.

18. The preparation method of the Ag-CoFe alloy@NC composite CDI material as described in claim 17, characterized in that, The roasting temperature is 480~520℃.

19. The preparation method of the Ag-CoFe alloy@NC composite CDI material as described in claim 7, characterized in that, The roasting time is 2-4 hours.

20. The application of the Ag-CoFe alloy@NC composite CDI material according to any one of claims 1 to 6 or the Ag-CoFe alloy@NC composite CDI material prepared by the preparation method according to any one of claims 7 to 19, characterized in that, It is used as an active material for CDI.

21. The application of the Ag-CoFe alloy@NC composite CDI material as described in claim 20, characterized in that, It was used as a CDI active material for the electro-adsorption of halide anions.

22. The application of the Ag-CoFe alloy@NC composite CDI material as described in claim 21, characterized in that, Halogen anions include chloride ions.

23. A CDI electrode material, comprising an active material, characterized in that, The active material comprises the Ag-CoFe alloy@NC composite CDI material according to any one of claims 1 to 6 or the Ag-CoFe alloy@NC composite CDI material prepared by the preparation method according to any one of claims 7 to 19.

24. The CDI electrode material as described in claim 23, characterized in that, In the active material, the content of the Ag-CoFe alloy@NC composite CDI material is above 70 wt.%.

25. The CDI electrode material as described in claim 23, characterized in that, The CDI electrode material also includes a binder and a conductive agent.

26. A CDI electrode, comprising a current collector and a CDI electrode material composite thereon, characterized in that, The CDI electrode material is the CDI electrode material according to any one of claims 23 to 25.

27. A CDI device, characterized in that, It includes the CDI electrode as described in claim 26.

Citation Information

Patent Citations

  • Preparation method and application of novel chloride ion removal material Ti3C2Tx / Ag

    CN111777068A

  • Preparation and application method of silver-carbon composite electrode material

    CN113257586A

  • Silver nanowire-lignin derived carbon composite aerogel as well as preparation method and application thereof

    CN115463625A

  • Co3Fe7 alloy / C composite CDI active material, preparation thereof and application of Co3Fe7 alloy / C composite CDI active material in ionic electro-adsorption

    CN115312741A

  • Carbon-impregnated iron coated C / N-C composite CDI electrode active material and preparation and application thereof

    CN116212816A